Analysis of Calculating the Cost of Goods Production Using the Full Costing Method in Determining Selling Prices at Jepara Furniture Stores (Case Study at the Bondan Sari Furniture Store, Karawang Regency, 2019 - 2021) - Wahyuni, Dian Try Ananda; Sihabudin, Sihabudin; Fauji, Robby (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research was conducted to analyze the cost of production using the full costing method in determining the selling price of Bondan Sari Furniture. The research was conducted on Jl. Ir. H. Juanda, No. 69, Cikampek Karawang. The data analysis technique used in this research is descriptive quantitative analysis using the full costing method. The results of the calculations show that the calculation of the cost of production and selling prices using the full costing method is higher than the company's calculations. This is because full costing calculates all costs in detail both fixed and variable costs and in determining the selling price full costing calculates non-production costs.